Diversity reportage in Aotearoa: Demographics and the rise of the ethnic media - David Robie (Asia Pacific Network, 2009)
For more than two decades, diversity has been a growing mantra for the New Zealand news media. Initially, the concept of biculturalism—partnership with the indigenous tangata whenua—was pre-eminent in the debate, but as the nation’s Pasifika and ethnic media have flourished and matured and demographics have rapidly changed, multiculturalism has become increasingly important and challenging. The regional media relationship in the context of contested notions such as the ‘arc of instability’ and the impact of coups and crises on journalists has become critical. Projected demographics by Statistics New Zealand indicate that the country’s Asian population will almost double by 2026. The Pasifika and Māori populations are also expected to grow by 59 and 29 per cent respectively. Māori, Pasifika and ethnic media in Aotearoa/New Zealand are also steadily expanding with implications for the media industry and journalism educators. This article examines the regional trends and how initiatives such as the Pacific Media Centre and new journalism courses with an emphasis on diversity are addressing the challenges.